COMMUNICATION AND INFORMATION TECHNOLOGY (CIT), COLLABORATIVE AUTHORSHIP AND KNOWLEDGE PRODUCTION IN TERTIARY EDUCATION - Dóris Maria Luzzardi Fiss; Israel da Silva Aquino (Editora da Universidade de Santa Cruz do Sul, 2013)
The present article approaches a research developed in the period of 2009-2012 along with licensees from Universidade Federal do Rio Grande do Sul that analyses the role of Virtual Learning Environments as tools of interaction and their effects in the production processes of public knowledge student involved from the perspective of collaborative authorship. It seeks to identify their potential as curriculum, learning and affective tools that enable the construction of qualitatively different relationships. It was sought to achieve these objectives throughout the analysis of the data generated by questionnaires, completing related aspects of the digital resources use in its academic path. We work with 28 selected reports, confronting these data to the theoretical matrix - Cesar Coll, Luciana de Souza Gracioso, Gustavo S. Saldanha and José Armando Valente. This work revealed that the use of other tools as the Virtual Learning Environments enabling the creation of learning dynamics as well as new ways of interaction between the participants modifying partially its learning processes from the offered possibilities.